Professional mental health support seeking in Women of Refugee Background resettled in Australia: An exploratory study of facilitators and barriers. (2nd April 2021) - Hawkes, Clare; Norris, Kimberley; Joyce, Janine; Paton, Douglas
Abstract: The present study is the first to investigate factors influencing professional mental health support seeking in Women of Refugee Background (WoRB) in Australia. WoRB are a vulnerable population with a range of complex mental health needs. Despite this, research has indicated that WoRB are an underrepresented population in the utilisation of mental health support services. This is a particular concern in Australia, due to an increasing number of WoRB being resettled. A multivariate logistical regression was conducted on a sample of 450 WoRB resettled in Australia from the Building a New Life in Australia (BNLA) data set to investigate factors associated with seeking professional mental health support. Several factors were identified as being significantly associated with professional mental health support seeking in WoRB resettled in Australia, including age, resettlement location, marital status, prearrival trauma involving violence against women, language barriers and health‐related variables, including mental distress and long‐term disability. The current study provides a unique insight into professional mental health support seeking from a gendered perspective in WoRB resettled in Australia. Insights into factors that influence seeking professional mental health support in this highly vulnerable population must inform mental health practice, service delivery and policies.